A Research of Theses Related to Alevism in Universities of Turkey (1990-2020) - Kocak, Aynur; Koc, Almira (Rector CIU Cyprus Int Univ, 2021)
The Alevi society, which has transferred its culture, belief and lifestyle to future generations mainly through oral culture since its emergence, has attracted the attention of various researches over the years. When the history of the Alevi culture, which has spread to many regions of the world from Anatolia, the Middle East, Europe to America, is examined, it is seen that they continue their existence in Anatolia to a great extent. In Turkey and as well as in other countries, Alevi culture attracted the attention of many researches, especially in the context of the social sciences has been the focus of different research disciplines. These studies considerably with interdisciplinary studies. This study examined the studies related to Alevism between postgraduate theses at universities in Turkey between the years 1990-2020; according to years, provinces, discipline weights, methods used and subjects. The theses made in this study are classified under general titles according to their subjects. The data of studies on Alevism between 1990-2020 have ben visualized through graphics. Then, these graphics were interpreted in the light of the data obtained through the literature review.
Keywords: Alevism; Qizilbash; university; postgraduate; scientific thesis; Arts & Humanities - Other Topics; Literature